Human Capital and Its Developing Factors - Sharipov Mirzoxid Latifovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
In the article, concepts are discussed historically and focuses on two major components of human capital, education and training, and health. The institutions that encourage human capital investment are discussed, as is the role of human capital in economic growth. The notion that the study of human capital is inherently historical is emphasized and defended.